Digital Health Literacy and Health Information Seeking Behavior among Adolescents in Indonesia - Sutha, Diah Wijayanti; Christine; Novianti, Siti; Solihin, Asri Handayani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: The widespread use of the internet among adolescents has transformed how they access health information. However, the abundance of unverified online content poses risks for individuals who lack the skills to assess its credibility. Digital health literacy is therefore essential for enabling adolescents to seek, evaluate, and use health information responsibly. Objectives: This study examined the relationship between digital health literacy and health information–seeking behavior among Indonesian adolescents, providing empirical evidence to inform digital health promotion strategies. Methods: A cross-sectional analytic study was conducted with 524 adolescents aged 12–19 years from five provinces in Indonesia. Data were collected using an online questionnaire comprising the eHealth Literacy Scale (eHEALS) and a Health Information–Seeking Behavior (HISB) instrument developed by the researchers. Descriptive statistics were used to profile respondents, and Spearman’s rank correlation was applied to assess the relationship between variables. Results: Overall, 38.2% of adolescents demonstrated high, 46.7% moderate, and 15.1% low digital health literacy. Adolescents with higher literacy levels exhibited more active and critical health information–seeking behavior, including more frequent use of credible sources, information verification, and appropriate application of information in decision-making. A significant positive correlation was found between digital health literacy and health information–seeking behavior (ρ = 0.307; p = 0.007), indicating that digital health literacy substantially influences adolescents’ engagement with online health information. Conclusion: Digital health literacy plays an important role in shaping adolescents’ health information–seeking behavior. Strengthening digital health literacy should be prioritized in health promotion initiatives targeting young populations in the digital era.